СТАТИСТИЧЕСКИЙ АНАЛИЗ СТРУКТУРЫ ЗЕМЕЛЬ СЕЛЬСКОХОЗЯЙСТВЕННОГО НАЗНАЧЕНИЯ - Lyudmila G. Moisejkina; Ekaterina S. Darda (Статистика и экономика, 2016)
This article deals with the state and changes in the qualitative composition of the land in general and in particular for agricultural purposes. The factors contributing to the degradation of the land fund in Russia. The structure of changing the composition of cultivated areas in recent years.